How suboptimal is suboptimal choice?. Issue 1 (January 2017) - Hinnenkamp, Jay E.; Shahan, Timothy A.; Madden, Gregory J.
Abstract : In a frequently used suboptimal‐choice procedure pigeons choose between an alternative that delivers three food pellets with p = 1.0 and an alternative that delivers ten pellets with p = 0.2. Because pigeons reliably choose the probabilistic (suboptimal) alternative, the procedure has been proposed as a nonhuman analog of human gambling. The present experiments were conducted to evaluate two potential threats to the validity of this procedure. Experiments 1 and 2 evaluated if pigeons obtained food at a lower unit price (i.e., pecks per pellet) on the suboptimal alternative than on the optimal alternative. When pigeons worked under this suboptimal procedure they all preferred the suboptimal alternative despite some pigeons paying a higher price for food on that alternative. In Experiment 2, when the unit price ratio more closely approximated the inverse of the expected value ratio, pigeons continued to prefer the suboptimal alternative despite its economic suboptimality. Experiment 3 evaluated if, in accord with the string‐theory of gambling, the valuation of the suboptimal alternative was increased when pigeons misattributed a subset of the suboptimal no‐food trials to the optimal alternative. When trial sequences were arranged to minimize these possible attribution errors, pigeons still preferred the suboptimal alternative. These data remove two threats to the validity of the suboptimal choice procedure; threats that would have suggested that suboptimal choice reflects economic maximization.